A biorefinery approach to microbial oil production from glycerol by Rhodotorula glutinis. (June 2016) - Karamerou, Eleni E.; Theodoropoulos, Constantinos; Webb, Colin
Abstract: The use of biodiesel-derived glycerol as a carbon source for microbial oil production is a biorefinery engineering strategy that aims to reduce the glycerol surplus and make the microbial oil process more cost-effective. In this work, glycerol was used as the sole carbon source for the cultivation of the oleaginous yeast Rhodotorula glutinis along with only yeast extract as a nutrient supply and without pH control. Shake-flask cultivations showed that the specific growth rate and glycerol consumption of Rhodotorula glutinis were higher at lower glycerol concentrations (≤40 g L −1 ), while higher C/N atom ratios enhanced oil content. The present study extends the knowledge on the influence of the aeration rate and oxygen supply in cellular growth rate and microbial oil production, providing a wiser use of glycerol as an attempt to further reduce process costs. Cultivations at different air flow rates were performed in a 2 L bioreactor and showed that a low aeration rate of 0.5 L min −1 gave the best glycerol and nitrogen uptake rates, resulting in the highest growth (5.3 g L −1 ) and oil mass fraction (33% of the dry cell weight). A further 68% increase in cellular growth (16.8 g L −1 ) and a 34% oil mass fraction of the dry cell weight was achieved after applying a feeding strategy targeting combined growth and oil production. Graphical abstract: Highlights: Microbial oil production was enhanced in a simple two-stage fed-batch cultivation. 33% cellular lipid content was achieved under low pH conditions on a simple medium. Growth, nutrient uptake and oil production are stimulated by a low aeration rate. Growth of oleaginous yeast improved by 68% under fed-batch cultivation.